До видового складу кліщів-фітосеїд (Parasitiformes, Phytoseiidae) Національного природного парку «Ічнянський» (Чернігівська обл., Україна) - Bondarev, V. Yu.; Pasechnik, S. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
New data on the species composition and distribution of phytoseiid mites (Parasitiformes, Phytoseiidae) in plant associations of the National Nature Park “Ichnyansky” were obtained. Twenty species from 9 genera of the family Phytoseiidae are recorded: Amblyseius andersoni, Amblyseius herbarius, Amblyseius obtusus, Amblyseius rademacheri, Neoseiulus danilevskyi, Neoseiulus reductus, Neoseiulus zwoelferi, Euseius finlandicus, Kampimodromus aberrans, Kampimodromu corylosus, Dubininellus echinus, Dubininellus juvenis, Typhloctonus tiliarum, Amlydromella halinae, Amlydromella pirianykae, Amlydromella rhenana, Amlydromella clavata, Amlydromella verrucosa, Typhlodromus laurae, Galendromus longipilus. The calculation of the occurrence index (P1, %) of the identified species of phytoseiid showed that its maximum value is observed in E. finlandicus. This species is also the most numerous in the total number of collected specimens in the sample. Kampimodromus aberrans, D. juvenis, G. longipilus, K. corylosus, N. danilevskyi, N. zwoelferi and T. tiliarum should be considered as the most rarely encountered species with index of occurrence of 1.3%. The remaining species have intermediate values of this index. The analysis of literature data on the occurrence of phytoseiid species with the highest value of the index of occurrence (E. finlandicus, A. pirianykae and A. andersoni) in the plant associations of adjacent zones (Polesie and Steppe Zone) allowed us to reveal some regularities. In Polesie, E. finlandicus (Kolodochka, 2011) is the most common species. In the Steppe zone, E. finlandicus also has a high index of occurrence and is the third most common species of predatory phytoseiid mites. Such a high occurrence of this species is caused by a wide range of its potential victims. Euseius finlandicus is an euribiont, however more adapted to shrub vegetation. The decrease in the occurrence index of this species from Polesie to the Steppe Zone is explained by changes in the moisture content of biocenoses, as well as due to the gradual replacement of tree-shrub vegetation of grass. Amlydromella pirianykae and Amblyseius andersoni are found mainly on herbs. The detection of these species on trees and shrubs should be considered as incidental finds. The characteristic biocenoses for these species are the wet bayrachnye forests, floodplains of rivers, meadows. When choosing a biocenosis for habitat, humidity plays a key role. The analysis of the phytoseiid mites species complex in the plant associations of the Ichnyansky National Natural Park showed the presence of one dominant species, one subdominant, five types of first order subdominant and 13 minor community members in the community.